(untitled) (Journal of Atomic and Molecular Sciences, 2010)
Fourier-transform infrared spectroscopy has been used for the first time to study the adsorption of chlorofluoromethane (CH_2ClF) on TiO_2 at room temperature. The obtained spectra allow to deduce that the adsorbate-substrate interaction occurs through both the Cl and F atoms of the molecule and the surface Lewis acid site (Ti^4+) and by means H-bonds involving the CH_2 group and the surface Lewis basic sites (O^2- or OH^-). In order to better comprehend these interactions, a periodic quantum-mechanical study at DFT/B3LYP level has been carried out by considering the anatase (101) surface and focusing the attention on the determination of the energetically possible adsorbate-substrate structures. According to the comparison between the experimental and calculated vibrational frequencies, it can be concluded that the molecule can adsorb on the surface both through the Cl atom and an H-bond and by means the F atom and two H-bonds.